East Asian Preferential Trade Agreements in Services : Liberalization Content and WTO Rules - Fink, Carsten (2012)
The past seven years have seen a rapid proliferation of preferential trade agreements (PTAs) in the East Asian region. Many of the recently concluded PTAs are comprehensive in their coverage, seeking not only the dismantling of barriers to trade in goods but also the liberalization of trade in services. This paper offers an assessment of this recent wave of services agreements in East Asia, focusing on their liberalization content and their compliance with WTO rules on regional integration. It draws on a database in which the authors recorded the value added of PTA liberalization undertakings relative to pre-existing multilateral services commitments. Among other things, this database is used to empirically assess the effect of the scheduling approach on the depth and breadth of liberalization undertakings.